Altered large-scale organization of shape processing in visual agnosia. (August 2020) - Freud, Erez; Behrmann, Marlene
Abstract: Recent findings suggest that both dorsal and ventral visual pathways process shape information. Nevertheless, a lesion to the ventral pathway alone can result in visual agnosia, an impairment in shape perception. Here, we explored the neural basis of shape processing in a patient with visual agnosia following a circumscribed right hemisphere ventral lesion and evaluated longitudinal changes in the neural profile of shape representations. The results revealed a reduction of shape sensitivity slopes along the patient's right ventral pathway and a similar reduction in the contralesional left ventral pathway. Remarkably, posterior parts of the dorsal pathway bilaterally also evinced a reduction in shape sensitivity. These findings were similar over a two-year interval, revealing that a focal cortical lesion can lead to persistent large-scale alterations of the two visual pathways. These alterations are consistent with the view that a distributed network of regions contributes to shape perception.